Microcredit, personal empowerment and quality of life of women borrowers – a theoretical framework - Fayyaz, Sana (Center for Sustainabality Research & Consultancy, 2015)
The issue of marginalization of women in development, particularly in South Asia, has been highlighted in the development literature. Women in this region are found to be generally poor, lack of education, and have a low quality of life, due to various economic and cultural reasons. Thus, unlocking the potentials of these women appears to be a plausible move as this could improve not only their income, but also their quality of life.One such initiative to unlock the potential of these women is micro credit program, where small loan is given to these women to enable them to embark on economic activities, which consequently improve their household income and quality of life.Indeed, there have been many studies that examine the relationship between micro credit and quality of life, and found that there is a positive relationship between micro credit and quality of life of the borrowers (women). However, most of these studies implicitly assume that the impact of micro credit on quality of life is direct, and hence, did not consider the role of other factors in evaluating the impact of micro credit on quality of life. Here, we argue that, the impact of micro credit on quality of life is not direct, but rather indirect.We believe personal empowerment does play an important role in influencing the impact of micro credit on quality of life.The mere availability of micro credit, in our view, did not guarantee a positive impact on quality of life. Rather, the availability of credit to borrowers affects their personal confidence, which consequently affects their level of quality of life.This paper discusses the theoretical framework by which these variables – microcredit, personal empowerment and quality of life – are inter-related.